Strategic Alliances: For Competition and Co-operation - Tripathy, Pratap Chandra (Indian Journal of Marketing, 2004)
For alliances to succeed, "You have to suppress the egoâ€¦.Its absolute poison in a joint venture" Lord Weinstock, the Managing Director of General Electric Company (U.K) The disadvantageous factors of acquisitions and mergers (A & Ms) have really broadened the scope of strategic alliance (SA). Factors like high cost Of acquisitions, the taken over problems of the acquired firm and the difficulties in integrating the acquired firm in the parent company’s organizational set up are sometimes distracting. Out of all the strategies (innovation, integration, RSD, ASM, SA) available, the scope of the present study is limited to SA only. The basic idea of choosing SA is that the same has emerged as the latest tool and has been becoming more popular in multinational business horizon.